Hubungan Komitmen Organisasi Dengan Organizational Citizenship Behavior (OCB) Pada Anggota Forum Anak Kota Banjarmasin - Annisah Ahmadya; Ceria Hermina; Dyta Setiawati Hariyono (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Teenagers are a valuable assets in shaping the future of a country. Teenage participation in education and social activities is very important. The government facilitates this by providing participation forums such as the children’s forum. The aim of this research is to determine the relationship between organizational commitment and organizational citizenship behavior (OCB) among members of the Banjarmasin City Children's Forum. This research uses quantitative methods with a correlational approach. This research found that there is a significant relationship between organizational commitment and organizational citizenship behavior (OCB) among members of the Banjarmasin City Children's Forum. The results of the hypothesis test show a sig. (2-tailed) is 0.003, which indicates significant and a positive relationship between the two variables with a correlation coefficient of 0.294. These results indicate that the higher the organizational commitment, the higher the OCB, and vice versa, namely the lower the organizational commitment, the lower the OCB.